Associations of chronotype, Big Five, and emotional competences with perceived stress in university students. (2nd July 2020) - You, Min; Laborde, Sylvain; Dosseville, Fabrice; Salinas, Agnès; Allen, Mark S.
ABSTRACT: This study aimed to investigate the associations between individual difference factors (chronotype, Big Five, emotional competences) and perceived stress in French university students. In total, 362 students agreed to take part ( M age = 20.19 ± 1.75 years). Participants completed the Caen Chronotype Questionnaire, Big Five Inventory, the Profile of Emotional Competences, and the Perceived Stress Scale. Results showed that chronotype amplitude (+), eveningness chronotype (+), neuroticism (+), conscientiousness (-), and intrapersonal emotional competences (-) were important for perceived stress. These findings have theoretical and practical implications in terms of identifying students who might benefit most from stress management interventions.